Jennifer Twyman & Jacqueline Ashby bust myths about gender, farming and climate change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
At the cutting edge: current knowledge on closing the gender gap in farming under climate change Keynote presentation by Jacqueline Ashby, CGIAR Senior Advisor on Gender and Research and Jennifer Twyman, Gender Specialist, CIAT, at the seminar on Closing the gender gap in farming under climate change held 19 March 2015 in Paris Read more about the event: https://ccafs.cgiar.org/events/closing-gender-gap-farming-under-climate-change-new-knowledge-renewed-action